Metabolomic profile of term infants of gestational diabetic mothers. (April 2014) - Dani, Carlo; Bresci, Cecilia; Berti, Elettra; Ottanelli, Serena; Mello, Giorgio; Mecacci, Federico; Breschi, Rita; Hu, Xiaoyu; Tenori, Leonardo; Luchinat, Claudio
Abstract Objective: Maternal diabetes increases the risk of perinatal mortality and morbidity, but the maintenance of antenatal normal glucose serum prevents the majority of neonatal complications. The aim of our study is to compare the metabolomic profile of infants of gestational diabetic mothers (IGDMs) to that of infants of healthy mothers to evaluate if differences remain despite a strict control of gestational diabetes. Methods: We performed the metabolomics study in cord serum sampled from 30 term IGDMs and 40 controls recording the occurrence of the most frequent complications in IGDMs. Results: We demonstrated that IGDMs have lower level of glucose and higher level of pyruvate, histidine, alanine, valine, methionine, arginine, lysine, hypoxanthine, lipoprotein and lipid than controls, but we did not find any clinical differences. Conclusions: Our results suggest that prolonged fetal exposure to hyperglycemia during pregnancy can change neonatal metabolomic profile at birth without affecting the clinical course.